Cold War science and the transatlantic circulation of knowledge - Dongen, Jeroen van, 1974- (History of science and medicine library, 2015)
"Cold War Science and the Transatlantic Circulation of Knowledge delves into how the Cold War, as a global phenomenon, shaped local conditions and decisions for science in light of US-Europe relationships. The articles in this volume, edited by Jeroen van Dongen (University of Amsterdam & Utrecht University), show how the Western network in which science was circulated and produced was strongly conditioned by the state and its international relations. The workings of secrecy, the consequences of US hegemony and decolonization, and the ambitions of post-war recovery attempts were all mediated through the interference of the state and through its relative position in the network. At the same time, hubristic expectations prefigured in the state's relation to science"--Provided by publisher.